AMNIOSENTESIS: TINJAUAN MENYELURUH - Marshaly Safira Masrie; Jonas Nara Baringbing (Bahasa Indonesia, 2020)
Introduction: Amniocentesis is an invasive procedure that removes the amount of amniotic fluid to obtain fetal cells to chromosomal examination. It's one of the prenatal diagnostic techniques and methods introduced during the last ten years. This practice is essential to present because of the large incidence of chromosomal abnormalities in infants, which is 90 events per 10,000 births.Objective: This article is used as a learning material to increase insight regarding amniocentesis, which is the most frequently used invasive prenatal diagnostic method. Amniocentesis has a reasonably high success rate and helps prevent and detect early hereditary diseases and congenital abnormalities in the unborn fetus.Method: The writing of this article used the narrative review method as part of the literature studyDiscussion: Amniocentesis has other purposes, such as fetal lung maturity level assessment, and determines whether fetal infection occurred. The amniocentesis procedure is usually done at 15-20 weeks' gestation. If the amniocentesis procedure is performed earlier than 15 weeks' gestation, the risk of pregnancy loss increases. Amniotic fluid phospholipid analysis can determine the degree of fetal lung maturation. Amniotic fluid can also be used for biochemical analysis, molecular studies, and microarray chromosome analysis (CMA).